Clinicopathological significance of preoperative thrombocytosis in patients with epithelial ovarian cancer - Yeasmin, Sabiha; Khatun, Sabera; Khatoon, Farhana; Sultana, Nadira; Sarker, Reeta Rani; Yeasmin, Nahida; Siddique, Abu Raihan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Reactive thrombocytosis is reported in a variety of solid tumors. A few studies have documented preoperative thrombocytosis in ovarian cancer. Methods: This was a cross-sectional study conducted in the Department of Gynaecological Oncology, Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh, during January to December 2019. A total of 94 patients with epithelial ovarian cancer between 18-70 years of age who underwent primary surgical treatment were included in this study. Chi-square tests were done to see the significance of differences between the two groups where p<0.05 considered as the level of significance with 95% CI. Results: The mean age was 45.39±13.23 years in the thrombocytosis and 48.98±15.46 years in without thrombocytosis group with a range of 18 to 70 years (p=0.231). The difference in education and occupation were statistically significant (p<0.05) between the two groups. The mean Hb% was 10.02±1.47 (gm/dl) in thrombocytosis and 11.15±1.52 (gm/dl) without thrombocytosis group. The difference was statistically significant (p<0.001) between two groups. The study showed that 30 (75.0%) patient’s serum CA-125 was >500 in the thrombocytosis group and 9 (16.7%) in the without thrombocytosis group (p=0,001), OR=15.0, 95.0% CI=4.92 to 47.72, p=0.001. Optimal cytoreduction between two groups were observed statistically significant (p=0.004), OR=3.49, 95.0% CI=1.33 to 9.28. The difference of grade of tumor observed statistically significant between the groups (p=0.022). The 11 (27.5%) patients had lymph node metastasis in thrombocytosis group and 6 (11.1%) in without thrombocytosis, OR=3.03, 95.0% CI=0.91 to 10.48, p=0.022. The OR of developing lymph node metastasis was 3.03 times higher in the thrombocytosis group. Conclusions: Thrombocytosis was commonly detected in preoperative evaluation of women diagnosed with epithelial ovarian cancer. Anemia, higher serum CA-125 level >500, sub-optimal cytoreduction, advanced stage disease, higher grade tumor, and lymphnode metastasis were significantly more frequent in patients with thrombocytosis.